Psychological effects of the earthquake disaster in Türkiye: a serial mediating model - Kocyigit, Busra; Ceco, Gamze; Satici, Seydi Ahmet; Deniz, M. Engin (SPRINGER, 2024)
On February 6, 2023, two major earthquakes with epicenters in southeastern T & uuml;rkiye, measuring 7.7 and 7.6 magnitudes respectively, devastated widespread areas. Research suggests that survivors of natural disasters including earthquakes have increased trauma and anxiety responses. Due to the negative psychological effects of the earthquake, it is necessary to examine the factors that improve mental health. This study aimed to assess the mediating role of coping flexibility and emotion dysregulation in the relationship between post-traumatic stress symptoms (PTSS) and anxiety responses (GAD). Within the framework of the study, 596 people affected by the earthquake completed the scales (298 Females and 298 Men; age mean: 32.09). Data were collected online from the convenience sampling method. Reliability-measured scales were used to measure the level of being affected by the earthquake, severity of anxiety, coping flexibility, and emotional dysregulation. The structural equation modeling indicated that the mediating role of coping flexibility and emotion dysregulation was significant in the relationship between post-traumatic stress symptoms (PTSS) and general anxiety disorder (GAD). The presence of posttraumatic symptoms was associated with lower coping flexibility, greater difficulties in emotion regulation, and higher levels of anxiety. After two catastrophic earthquakes, there is a risk of long-term deterioration of individuals' mental health. This study may be considered when implementing interventions for the mental health of individuals affected by the earthquake.
Keywords: Earthquake; Trauma; Anxiety; Coping flexibility; Emotion dysregulation; POSTTRAUMATIC-STRESS-DISORDER; PTSD; SYMPTOMS; DIFFICULTIES; DEPRESSION; ADOLESCENTS; SURVIVORS; Psychology